Multilateral Trade Law at a Crossroads: Legal Perspectives on WTO Reforms and Institutional Resilience or Multilateral Trade Law at a Crossroads: WTO Reform, Pandemic Lessons, and Legal Resilience - Pusapati, Uma; Lakshmi, V Vijay (Journal of Neonatal Surgery, 2025)
The World Trade Organization (WTO) has long functioned as the central forum for global trade governance. However, in recent years, its efficacy has been increasingly questioned, particularly with the paralysis of its Appellate Body. This paper critically examines the institutional deficiencies of the WTO’s Dispute Settlement Mechanism (DSM), the rise of plurilateral negotiations, and contentious debates surrounding special and differential treatment. The analysis draws on recent ministerial outcomes, including those from the 13th Ministerial Conference (MC13), and recent developments such as the resurgence of tariff-based trade conflicts involving the United States. The study argues for a comprehensive and inclusive reform agenda, emphasizing procedural functionality, legitimacy, and adaptability to evolving trade dynamics. Research Methodology This study employs a qualitative legal analysis combined with a policy-based approach. Primary sources include WTO ministerial declarations, official documents, and agreements, particularly outcomes from the 13th Ministerial Conference (MC13). Secondary sources encompass peer-reviewed journal articles, institutional policy briefs, and reports from global economic organizations. The research critically evaluates the legal structure of WTO mechanisms, interprets member positions on reform, and identifies systemic challenges through a combination of doctrinal analysis and comparative assessment. This methodology provides both normative insights and contextual understanding of evolving multilateral trade dynamics.